Concurrent imaging of synaptic vesicle recycling and calcium dynamics. - Li, Haiyan; Foss, Sarah M.; Dobryy, Yuriy; Park, C. Kevin; Hires, Samuel A.; Shaner, Nathan C.; Tsien, Roger Y.; Osborne, Leslie C.; Voglmaier, Susan M. (Frontiers in Molecular Neuroscience, 2011)
Synaptic transmission involves the calcium-dependent release of neurotransmitter from synaptic vesicles. Genetically encoded optical probes emitting different wavelengths of fluorescent light in response to neuronal activity offer a powerful approach to understand the spatial and temporal relationship of calcium dynamics to the release of neurotransmitter in defined neuronal populations. To simultaneously image synaptic vesicle recycling and changes in cytosolic calcium, we developed a red-shifted reporter of vesicle recycling based on a vesicular glutamate transporter, VGLUT1-mOrange2 (VGLUT1-mOr2), and a presynaptically-localized green calcium indicator, synaptophysin-GCaMP3 (SyGCaMP3) with a large dynamic range. The fluorescence of VGLUT1-mOr2 is quenched by the low pH of synaptic vesicles. Exocytosis upon electrical stimulation exposes the luminal mOr2 to the neutral extracellular pH and relieves fluorescence quenching. Re-acidification of the vesicle upon endocytosis again reduces fluorescence intensity. Changes in fluorescence intensity thus monitor synaptic vesicle exo- and endocytosis, as demonstrated previously for the green VGLUT1-pHluorin. To monitor changes in calcium, we fused the synaptic vesicle protein synaptophysin to the recently improved calcium indicator GCaMP3. SyGCaMP3 is targeted to presynaptic varicosities, and exhibits changes in fluorescence in response to electrical stimulation consistent with changes in calcium concentration. Using real-time imaging of both reporters expressed in the same synapses, we determine the time course of changes in VGLUT1 recycling in relation to changes in presynaptic calcium concentration. Inhibition of P/Q- and N-type calcium channels reduces calcium levels, as well as the rate of synaptic vesicle exocytosis and the fraction of vesicles released.